Maternal protein‐energy malnutrition during early pregnancy in sheep impacts the fetal ornithine cycle to reduce fetal kidney microvascular development. Issue 11 (30th July 2014) - Dunford, Louise J.; Sinclair, Kevin D.; Kwong, Wing Y.; Sturrock, Craig; Clifford, Bethan L.; Giles, Tom C.; Gardner, David S.
Abstract : This paper identifies a common nutritional pathway relating maternal through to fetal protein‐energy malnutrition (PEM) and compromised fetal kidney development. Thirty‐one twin‐bearing sheep were fed either a control ( n =15) or low‐protein diet ( n = 16, 17 vs. 8.7 g crude protein/MJ metabolizable energy) from d 0 to 65 gestation (term, ~ 145 d). Effects on the maternal and fetal nutritional environment were characterized by sampling blood and amniotic fluid. Kidney development was characterized by histology, immunohistochemistry, vascular corrosion casts, and molecular biology. PEM had little measureable effect on maternal and fetal macronutrient balance (glucose, total protein, total amino acids, and lactate were unaffected) or on fetal growth. PEM decreased maternal and fetal urea concentration, which blunted fetal ornithine availability and affected fetal hepatic polyamine production. For the first time in a large animal model, we associated these nutritional effects with reduced micro‐ but not macrovascular development in the fetal kidney. Maternal PEM specifically impacts the fetal ornithine cycle, affecting cellular polyamine metabolism and microvascular development of the fetal kidney, effects that likely underpin programming of kidney development and function by a maternal low protein diet.—Dunford, L. J., Sinclair, K. D., Kwong, W. Y., Sturrock, C., Clifford, B. L., Giles, T. C., Gardner, D. S., Maternal protein‐energy malnutrition during early pregnancy in sheep impacts the fetal ornithine cycle to reduce fetal kidney microvascular development. FASEB J. 28, 4880–4892 (2014). www.fasebj.org